Construction of mental health care based on the experiences of a nursing student - Danton Matheus de Souza; Gabriella de Andrade Boska; Mônica Silvia Rodrigues de Oliveira; Márcia Aparecida Ferreira de Oliveira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to report the experience of a nursing student with mental health care during a clinical internship. Method: an experience report based on data from a Singular Therapeutic Project developed by a nursing student during 16 days of practice in a Day Hospital as part of an undergraduate course. The findings were analyzed based on the theory of interpersonal relationships and psychosocial rehabilitation. Results: the care process was organized between the weeks and phases of the relationship in: 1) from the unknown to relationship of trust; 2) reflections and reframing as a care proposal; 3) from limitation to leading role; 4) from care resolution to mutual transformations. Final considerations: it was concluded that despite the limitations of the practice context, the student was able to conduct psychosocial interventions in mental health in line with the expected goals and produce meanings in both involved.